Distribution and function of plasmids in Salmonella enterica - Rychlík, Ivan; Gregorová, Daniela; Hradecká, Helena (Veterinary microbiology, 2006)
Plasmids of Salmonella enterica vary in size from 2 to more than 200 kb. The best described group of plasmids are the virulence plasmids (50-100 kb in size) present in serovars Enteritidis, Typhimurium, Dublin, Cholerae-suis, Gallinarum, Pullorum and Abortus-ovis. They all encode spvRABCD genes involved in intra-macrophage survival of Salmonella. Another group of high molecular weight plasmids are plasmids responsible for antibiotic resistance. Since most of these plasmids are conjugative, besides storage of genetic information, they contribute to the spread of genes in bacterial populations. The low molecular weight plasmids are the last group of plasmids found in S. enterica. Some of them have been shown to increase resistance to phage infection due to the presence of restriction modification systems. Despite limited knowledge on their function, their presence or absence is frequently used for strain differentiation in epidemiological studies.
Keywords: Molecular Weight; Plasmids; Animals; salmonelová infekce u zvířat; Virulence; Financing, Organized; Drug Resistance, Bacterial; Virulence Factors; plazmidy; Salmonella enterica; financování organizované; faktory virulence; Salmonella Infections, Animal; virulence; bakteriální léková rezistence; molekulová hmotnost; zvířata